KONSTRUKSI BUDAYA DAKWAH EMHA AINUN NADJIB DALAM ACARA MOCOPAT SYAFAAT SEBAGAI MEDIUM RESISTENSI - Insani, Nur Hanifah (Diksi, 2019)
(Title: Construction of Da'wah Culture Emha Ainun Nadjib in the "Mocopat Syfa'at" Event as a Medium of Resistance). This research studies about discourse performance of Mocopat Syafaat as a medium resistance into interesting study. This study tries to give focus to unpack and understand how texts of discourse performance and religious music are used to construct the voices of resistance and deal with changes in socio-cultural context and politics. Norman Fairclough critical discourse analysis with a qualitative approach is used to dig deeper the role of language in the construction of discourse performance of Mocopat Syafaat. This research findings suggest that the texts of the music and the contents discourse performance of Mocopat Syafaat is a powerful cultural form to ask or raise support for a movement or a case, build solidarity and social cohesion, or promote awareness. Keywords: da'wah cultural, discourse performance, Mocopat Syafaat, resistance